A posterior approach for curettage in giant cell tumor of bone in the proximal fibula - Sakamoto, Akio (J Surg Case Rep, 2019)
Giant cell tumor of bone (GCTB) is a locally aggressive tumor. En bloc resection to reduce the recurrence rate has a high risk of peroneal nerve paralysis and knee instability associated with collateral ligament resection. In the current report, the posterior approach to curettage is introduced in a 55-year-old male with GCTB in the proximal fibula. The approach makes a wide operative field for curettage of GCTB in the proximal fibula without dissecting the peroneal nerve. The approach would prevent postoperative peroneal nerve palsy and knee instability and possibly reduce recurrences.